2021
DOI: 10.32996/jweep.2021.3.7.2
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of Grammatical Errors in Written English of Libyan EFL Students with Special Reference to Arabic as their First-Language

Abstract: This study focuses on an exploration of grammatical errors in written English of Libyan EFL students with special reference to Arabic as their first language. One of the most important factors that negatively affect EFL students' writing is grammatical errors. Several studies have looked at grammatical errors made by learners of English as a foreign language. Some studies have reported that L1 interference has been indicated as an important factor in the commission of such errors. The current study explores th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…As errors undoubtedly occur in language learning and during the practice of writing in a foreign language (Thornbury, 1999), the different types of error were explored. Al Jawad and Mansour (2021) found that grammatical errors were common among Arabic native speakers learning to write in English. As for errors made by learners of writing in AFL, the findings of the current study are consistent with Alwaleedi et al ( 2019), who confirmed that similar learners have major problems with writing Arabic, including using some aspects of grammar, such as prepositions, definite and indefinite nouns, and using adjectives before nouns.…”
Section: Discussionmentioning
confidence: 99%
“…As errors undoubtedly occur in language learning and during the practice of writing in a foreign language (Thornbury, 1999), the different types of error were explored. Al Jawad and Mansour (2021) found that grammatical errors were common among Arabic native speakers learning to write in English. As for errors made by learners of writing in AFL, the findings of the current study are consistent with Alwaleedi et al ( 2019), who confirmed that similar learners have major problems with writing Arabic, including using some aspects of grammar, such as prepositions, definite and indefinite nouns, and using adjectives before nouns.…”
Section: Discussionmentioning
confidence: 99%